Progress on Pathogenesis Rccs and Related Treatments - Li , Yehao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Kidney cancer has been a concern by society for many years because the pathogenesis of kidney cancer is complex, it may be related to genetic factors, environmental factors and lifestyle. Early diagnosis is crucial for the treatment and prognosis of kidney cancer, but there are still certain challenges. Advances in kidney cancer include gene mutation research, immunotherapy, targeted therapy and liquid biopsy. These research advances are expected to provide more accurate and effective methods for the early diagnosis, treatment and prognosis assessment of kidney cancer. However, the research of kidney cancer still faces some challenges and unknown areas, including early diagnosis, drug resistance mechanism, metastasis mechanism and individualized treatment strategy. This essay is an analysis of the research of kidney cancer, which is about the factors of getting kidney cancer and the treatment of kidney cancer. Kidney cancer research can help improve early diagnosis and screening, gain insight into tumorigenesis mechanisms, overcome drug resistance and metastasis, and promote breakthroughs in immunotherapy. For future expectations, people should refine unclear mechanisms and improve treatment options.